Guidance on the Use of Gamification-Based Mobile Fitness Apps to Support Motor Development in Elementary School Children - M. Akbar Husein Allsabah; Sugito Sugito; Weda; Budiman Agung Pratama; Nur Ahmad Muharram; Yosi Anugrahani Maksum; Moh. Aan Zainul Arifin (GANDRUNG: Jurnal Pengabdian Kepada Masyarakat, 2026)
This community service program aimed to improve the capacity of teachers and parents in utilizing gamification-based mobile fitness as a medium to support physical activity and motor development among elementary school children. The program was conducted at SD Negeri Betet 3, Kediri City, involving physical education teachers, classroom teachers, parents, and students. The implementation consisted of six stages: needs assessment, program socialization, mobile fitness training, implementation assistance, monitoring, and evaluation. Activities focused on introducing mobile fitness applications, integrating gamification elements into physical activities, and assisting participants in applying movement-based activities at school and home. The results showed that the program was well received by participants, with a participation rate of 95%. All participating teachers were able to operate the main features of the mobile fitness application and independently design gamified movement activities. Participants reported that the program provided practical strategies for utilizing digital technology more positively, while students demonstrated higher engagement in physical activities delivered through challenges and game-based tasks. The program concluded that gamification-based mobile fitness can serve as an innovative approach to promoting active lifestyles and supporting motor development among elementary school children through collaboration between schools and families.